“Ich-Mupong”, a swollen stomach: an ethnographic study of the daily lived experiences of schoolchildren in schistosomiasis high transmission areas along Lake Albert, Hoima District - Paskari Odoi; Stella Neema; Fred Bateganya; Birgitte J. Vennervald; Shona Wilson (BMC Public Health)
Abstract Background Our primary focus was Schistosoma mansoni infection and schoolchildren. Within communities the social environment may promote individual risk of infection for the school-aged children. There will also be demographic groups who are not targeted or reached by preventive chemotherapy campaigns. The behaviours of these other groups will interact with those of school-aged children, resulting in further infection risk through exposure-related behaviours. Furthermore, perception of the disease may significantly influence the schoolchildren’s lived experience of the infection and associated disease. It is therefore crucial to document the daily experiences of schoolchildren living in schistosomiasis high transmission areas along Lake Albert, Hoima District. Methods An ethnographic study explored schoolchildren’s perspectives and daily life organisations that shape their risk of schistosomiaisis and their perceptions of the disease. The study was conducted between November 2022 and August 2023. It involved in-depth interviews with schoolchildren and their parents, key informant interviews, focus group discussions with schoolchildren, and participant observations. Data was analysed using a reflexive thematic analysis. Code reports were generated inductively using ATLAS.ti (Version 7). Results The study revealed a significant level of knowledge and awareness about schistosomiasis among schoolchildren. They had understanding of the risk factors, continued exposure, and experiences of illness, though they had little autonomy to address these through their own behaviour as they were influenced by the behaviour of others and macro-factors such as WASH provision and economic need. Study participants experienced individual-level effects of schistosomiasis such as educational impacts and isolation as a significant form of stigma. Conclusions There is a need for continued community sensitisation and awareness campaigns to address social stigma, educational impact, and contamination and exposure-related behaviours. National and regional policies and programmes on WASH, livelihood and poverty eradication programmes need to be revisited in schistosomiasis high transmission areas to help provide alternatives and improve schoolchildren’s lived experiences. Clinical trial number Not applicable.